A Rare Triterpenoidal Saponin Isolated and Identified from Tetraena simplex (L.) Beier &Thulin (Syn. Zygophyllum simplex L.). Issue 6 (12th February 2020) - Baky, Mostafa H.; Gabr, Nagwan M.; Shawky, Enas M.; Elgindi, Mohamed R.; Mekky, Reham H.
Abstract: Tetraena simplex (L.) Beier & Thulin (syn. Zygophyllum simplex L.) is an annual, succulent plant belonging to family Zygophyllaceae. The plant grows in harsh environmental conditions and it is traditionally used as an analgesic and anti‐inflammatory agent. This study aims to isolate and identify phytochemical constituents of the n ‐butanol fraction of its aerial parts that was repeatedly chromatographed on Diaion HP‐20 and silica gel columns to yield a rare triterpenoidal saponin, 3‐ O ‐[ β ‐D‐glucopyranosyl‐(1→2)‐ β ‐D‐glucopyranosyl] quinovic acid‐28‐ O ‐ β ‐D‐glucopyranosyl ester (1 ) along with three other known triterpenoidal compounds namely; 3‐ O ‐methoxy‐quinovic acid (2 ), quinovic acid (3 ), and 3‐ O ‐ β ‐D‐glucopyranosyl‐quinovic acid (4 ). Moreover, quercetin 3‐ O ‐ α ‐L‐rhamnoside (5 ) was isolated from this fraction. Different spectroscopic techniques including one dimensional (1D) and two dimensional (2D) NMR (Nuclear Magnetic Resonance) spectroscopy allowed the unambiguous structure elucidation of the isolated compounds. Abstract : The aerial parts of Tetraena simplex (L.) Beier & Thulin (syn. Z. simplex L.) were investigated for the presence of phytoconstituents. The results revealed that, five compounds from which four saponins in addition to one flavonoid glycoside were isolated and identified using different spectroscopic techniques. A rare triterpenoid saponin, 3‐ O ‐[ β ‐D‐glucopyranosyl‐(1→2)‐ β ‐D‐glucopyranosyl] quinovic acid‐28‐ O ‐ β ‐D‐glucopyranosyl ester along with four other compounds; 3‐ O ‐methoxy‐quinovic acid, quinovic acid, and 3‐ O ‐ β ‐D‐glucopyranosyl‐quinovic acid and quercetin 3‐ O ‐ α ‐L‐rhamnoside were isolated.